2020
DOI: 10.3390/ma13051040
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Depth of Cut in Single-Pass Grinding on the Microstructure and Properties of the C45 Steel Surface Layer

Abstract: The paper contains the results of a metallographic examination and nanoindentation test conducted for the medium carbon structural steel with low content of Mn, Si, Cu, Cr, and Ni after its grinding to a depth ranging from 2 μm to 20 μm, at constant cutting speed (peripheral speed) of vs = 25 ms−1 and constant feed rate of vft = 1 m/min. Applied grinding parameters did not cause the surface layer hardening, which could generate an unfavorable stress distribution. The increase in the surface hardness was obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The C45 steel is defined as a standard material for machinability in the state after normalization annealing [10]. Since the C45 steel was defined as an etalon for steel machining, many authors have analyzed different ways of machining and its influence on the dimension accuracy and resulting machined surface roughness [13][14][15][16][17]. It has been found that the grinding of the C45 steel causes a work hardening of its surface layer without phase transformation [17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The C45 steel is defined as a standard material for machinability in the state after normalization annealing [10]. Since the C45 steel was defined as an etalon for steel machining, many authors have analyzed different ways of machining and its influence on the dimension accuracy and resulting machined surface roughness [13][14][15][16][17]. It has been found that the grinding of the C45 steel causes a work hardening of its surface layer without phase transformation [17].…”
Section: Introductionmentioning
confidence: 99%
“…Since the C45 steel was defined as an etalon for steel machining, many authors have analyzed different ways of machining and its influence on the dimension accuracy and resulting machined surface roughness [13][14][15][16][17]. It has been found that the grinding of the C45 steel causes a work hardening of its surface layer without phase transformation [17]. A nanoindentation test on the cross-section, performed at a short distance from the grinded surface, has shown that ferrite grains were more susceptible to work hardening than pearlite grains due to the creation of an equiaxed cellular microstructure [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation